The Impact of Polyya's Problem-Solving Technique on Mathematical Problem-Solving Ability - Elvi Syahara Lubis; Dedy Juliandri Panjaitan (Edumaspul: Jurnal Pendidikan, 2025)
This development research generally aims to develop valid, practical and effective problem-based learning devices, specifically the objectives are to: 1) Produce valid, practical and effective problem-based learning device development products in improving students' mathematical problem-solving abilities and independence. 2) Analyze the improvement of students' mathematical problem-solving abilities in the application of problem-based learning devices. 3) Analyze the level of student learning independence in the application of learning devices. The researcher gave pretest questions to students to see the students' initial abilities before being given the developed learning devices. Data obtained from the pretest and posttest results were analyzed to determine how much increase in students' independent learning abilities occurred. The assessment instrument trial was conducted at the beginning (pretest) and at the end (posttest) of the meeting. This learning device was developed using a development model referring to Plomp's theory, which consists of five phases, namely the initial investigation research phase, design phase, design, assessment phase and implementation phase (trial). LKPD is another device developed with a problem-based learning model for the problem-solving abilities and independent learning abilities of participants. This can be said to be effective, valid and practical.